Education for the cultivation of emotions through textbooks: the example of Croatian high school history textbooks - Rona Bušljeta Kardum; Katarina Dadić; Martina Horvat (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - Contemporary teaching focuses on the students' active role in the acquisition of knowledge and largely neglects the role of emotions. Given the importance of empathy when it comes to the emotional development of the individual, and the opportunities offered by history as a subject with regard to encouraging empathy, the main purpose of research is to analyze the extent to which history textbooks contribute to empathy as one of key competencies of today's world. Materials/methods - In the research, qualitative and quantitative content analysis was used. The analysis includes only one didactic-methodical toolkit of the textbook - questions and tasks by the formulation of which it is possible to identify in which direction the teaching process "moves" and to what extent it encourages the cultivation of emotions. Results - The results suggest that high school history textbooks overemphasize the cognitive aspect of the learning process while simultaneously inadequately putting students in a position that would also allow them to be more emotionally engaged with the historical events and to thereby develop empathy. Conclusion - It is necessary to develop detailed guidelines with clear instructions on how to encourage students' emotional engagement in individual subjects and teaching units.